Constructing research questions doing interesting research - Alvesson, Mats, 1956-; Sandberg, Jorgen (SAGE, 2013)
All researchers want to produce interesting and influential theories. A key step in all theory development is formulating innovative research questions that will result in interesting and significant research. Traditional textbooks on research methods tend to ignore, or gloss over, actual ways of constructing research questions. In this text, Alvesson and Sandberg develop a problematization methodology for identifying and challenging the assumptions underlying existing theories and for generating research questions that can lead to more interesting and influential theories, using examples from across the social sciences. Established methods of generating research questions in the social sciences tend to focus on 'gap-spotting', which means that existing literature remains largely unchallenged. The authors show the dangers of conventional approaches, providing detailed ideas for how one can work through such problems and formulate novel research questions that challenge existing theories and produce more imaginative empirical studies. Constructing Research Questions is essential reading for any researcher looking to formulate research questions that are interesting and novel.